Sistem Pelayanan Akademik Terhadap Keluhan Mahasiswa Pada Perguruan Tinggi Untuk Mencegah Mahasiswa Berhenti Kuliah Dengan Metode Web Responsive Design - Hendri Hendri; Johni Paul Karolus Pasaribu (Jurnal Processor, 2022)
The current education industry in Indonesia continues to grow and competition is getting tougher so that more and more universities are competing to be able to provide better academic services to get students or prospective students. To be able to win the competition, universities must be able to provide maximum service quality. Good service will certainly make students feel comfortable and at home in the learning process at college so that it can reduce the number of students who stop studying, leave and drop out. Academic services as the core of business in universities must certainly be improved in order to increase the number of students who will enter the University. If the university does not know what the student's problems / obstacles are in the lecture process, it will certainly be difficult to find reasons why students drop out or why students leave. The purpose of this study is to create an academic service system for student complaints. It is hoped that the upper management of higher education can find out what problems / obstacles students are facing from the start so that they can prevent students from dropping out of college by providing correct solutions according to student needs.